Favourite music as an increasing factor of the result in the control running of athletes - Nagovitsyn, R. S.; Zekrin, F. H.; Fendel, T. V.; Zubkov, D. A.; Osipov, A. Y. (Journal of Human Sport & Exercise, 2019)
Background: Musical accompaniment of the implementation of physical exercises is interconnected with the motor activity of a person, which, as an art, can act through psychology and physiology to increase the athlete's result. The aim of the study was to analyse the influence of listening to your favourite music while running athletes of various qualifications at medium distances to increase the result in the control test. Study participants: athletes (14-18 years old): professional athletes involved in the athletics section "Athletics" (n=28), and amateur athletes engaged in other sports sections or not involved in sports sections at all (n=28). During the control test at medium distances, the athletes of the experimental group used special musical accompaniment. The results of the study. The implementation of a systematic training process in running and the use of special musical accompaniment when fulfilling the author`s conditions for its implementation during the control testing are significantly more effective (p<0.05). To a greater extent, to increase the result of athletes using musical accompaniment during the training process, and amateur athletes in the control test 2000 and 3000 meters (p<0.05), especially in the last third of the passage of the control distance. Findings. The practical significance and novelty of the work lies in the fact that the efficiency of playing music while running will be effective in the control test, if the author's development stated in the study is clearly taken into account.